2016
DOI: 10.1080/02508281.2016.1209284
|View full text |Cite
|
Sign up to set email alerts
|

The potential for craft brewing tourism development in the United States: a stakeholder view

Abstract: The craft brewing industry is experiencing growth worldwide; however, research on this industry has been scant in various domains, including research exploring the relationships between craft breweries and tourism. This study contributes to extant academic literature, investigating the perceived potential and challenges of craft brewing tourism (CBT) among 221 micro/small United States craft brewing operators. The study adopts stakeholder theory (ST) as the theoretical framework. Overall, participants perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Profit and return on investment should be investors’ main motivations, being dependent on relations with customers and tour operators. Craft brewers must capitalize on the global hype surrounding CB, which can be established through bars/pubs, excursion packs and CB food pairings (Alonso and Sakellarios, 2017). It has been shown that beer tourists’ motivations to visit a brewery are the CB experience, pleasure, socialization and beer consumption (Kraftchick et al , 2014).…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…Profit and return on investment should be investors’ main motivations, being dependent on relations with customers and tour operators. Craft brewers must capitalize on the global hype surrounding CB, which can be established through bars/pubs, excursion packs and CB food pairings (Alonso and Sakellarios, 2017). It has been shown that beer tourists’ motivations to visit a brewery are the CB experience, pleasure, socialization and beer consumption (Kraftchick et al , 2014).…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…Further investigation of the use of cross-sectional versus longitudinal research revealed that almost all studies are approached as a point-in-time investigation. It was found that very few use a longitudinal design to identify possible longitudinal trends and patterns of CBT (Alonso et al , 2016; Alonso and Sakellarios, 2017; Hermann et al , 2021; Sozen and O’Neill, 2020). These outcomes reflect that CBT literature still has several methodological gaps and that there is ample scope for future studies within the broader framework of CBT post-COVID-19 (Fountain, 2022).…”
Section: Overview Of Methodsmentioning
confidence: 99%
“…Their research into craft brewery tourism practices in the US and the UK confirms four market-based benefits: touring breweries, tasting bars and craft beer events (which encourage consumers to visit the brewery), promoting beer brand awareness and increasing sales. The relationship between craft breweries and tourism has been explored by Alonso & Sakellarios [50]. Participants in their research realized the potential of craft beer for tourism.…”
Section: Craft Beer Tourism As a Recognizable Chance For Sustainable Tourism Developmentmentioning
confidence: 99%